2020
DOI: 10.1021/acs.jpcc.0c04240
|View full text |Cite
|
Sign up to set email alerts
|

Li-Metal Anode in Dilute Electrolyte LiFSI/TMP: Electrochemical Stability Using Ab Initio Molecular Dynamics

Abstract: Ab initio molecular dynamics simulations were performed for Li+-conducting electrolytes based on trimethyl phosphates (TMP) and lithium bis­(fluorosulfonyl)­imide (Li+FSI–) salt in contact with a Li-metal electrode. We focused on the transient-state behavior at the electrolyte, interfacial electrolyte–Li-metal electrode, and lithium reference electrode–electrolyte–Li-metal electrode to study dynamics and activation energy barriers of the Li+ ion, electrochemical and thermal stability of the interface electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 80 publications
2
19
0
Order By: Relevance
“…[ 19a ] Computational simulations showed that the formation of SEIs will cause the open‐circuit potential energy of the Li‐metal electrode to drop by ≈0.42 eV compared with the average local potential profile of the pristine Li RE. [ 21 ] Thus, the Li‐metal electrode cannot serve as a versatile RE, and the as‐determined potentials of WE can be considerably varied in different electrolytes owing to the potential inconsistency of Li‐metal REs.…”
Section: Designmentioning
confidence: 99%
“…[ 19a ] Computational simulations showed that the formation of SEIs will cause the open‐circuit potential energy of the Li‐metal electrode to drop by ≈0.42 eV compared with the average local potential profile of the pristine Li RE. [ 21 ] Thus, the Li‐metal electrode cannot serve as a versatile RE, and the as‐determined potentials of WE can be considerably varied in different electrolytes owing to the potential inconsistency of Li‐metal REs.…”
Section: Designmentioning
confidence: 99%
“…Even rather elaborate electrode‐electrolyte/additive systems have been explored. [ 31 ] However, the size of the simulation systems and the time scales are far too small/short for proper statistical sampling of many interface properties and quantities of interest. Typically, the current state of the art is a thin small‐area electrode model with a dozen or fewer solvent molecules, and ions studied for some tens of picoseconds.…”
Section: Toward Inverse Design Of Battery Interfacesmentioning
confidence: 99%
“…[ 12 ] However, increasing electrolyte concentration does not always guarantee an elevated battery performance. Recent studies have shown that the wide‐temperature performance of Na‐ion batteries, [ 7c ] the rate performance of Li–S batteries, [ 13 ] and the cycling performance of Li metal batteries [ 5a,14 ] are greatly enhanced in the low concentration electrolytes. These discrepant conclusions indicate the necessity for a more thorough exploration of the underlying principles for electrolyte concentration regulation.…”
Section: Introductionmentioning
confidence: 99%